A Prospective Study of Musculoskeletal Outcomes Among Manufacturing Workers: II. Effects of Psychosocial Stress and Work Organization Factors. (February 2014) - Gerr, Fredric; Fethke, Nathan B.; Anton, Dan; Merlino, Linda; Rosecrance, John; Marcus, Michele; Jones, Michael P.
Objective: The aim of this study was to characterize associations between psychosocial and work organizational risk factors and upper-extremity musculoskeletal symptoms and disorders. Background: Methodological limitations of previous studies of psychosocial and work organizational risk factors and musculoskeletal outcomes have produced inconsistent associations. Method: In this prospective epidemiologic study of 386 workers, questionnaires to assess decision latitude ("control") and psychological job demands ("demand") were administered to study participants and were used to classify them into job strain "quadrants." Measures of job stress and job change were collected during each week of follow-up. Incident hand/arm and neck/shoulder symptoms and disorders were ascertained weekly. Associations between exposure measures and musculoskeletal outcomes were estimated with proportional hazard methods. Results: When compared to the low-demand/high-control job strain referent category, large increases in risk of hand/arm disorders were observed for both high-demand/high- control (hazard ratio [HR] = 4.49, 95% confidence interval [CI] = [1.23, 16.4]) and high-demand/low-control job strain categories (HR = 5.18, 95% CI = [1.39, 19.4]). Similar associations were observed for hand/arm symptoms. A strong association was also observed between the low-demand/low-control job strain category and neck/shoulder disorders (HR = 6.46, 95% CI = [1.46, 28.6]). Statistically significant associations were also observed between weekly stress level and weekly job change and several musculoskeletal outcomes. Conclusion: Associations between psychosocial risk factors and work organizational factors and musculoskeletal outcomes were large and in the hypothesized direction. Application: Prevention of occupational musculoskeletal disorders may require attention to psychosocial and work organizational factors in addition to physical factors. Methods to control adverse effects of psychosocial and work organizational risk factors should be explored.